Microphase transitions of block copolymer/homopolymer under shear flow - Guo, Y.; Zhang, J.; Wang, B.; Wu, H.; Sun, M.; Pan, J. (Condensed Matter Physics, 2015)
Cell dynamics simulation is used to investigate the phase behavior of block copolymer/homopolymer mixture subjected to a steady shear flow. Phase transitions occur from transverse to parallel and then to perpendicular lamellar structure with an increase of shear rate and this is the result of interaction between the shear flow and the concentration fluctuation. Rheological properties, such as normal stress differences and shear viscosity, are all closely related with the direction of the lamellae. Furthermore, we specifically explore the phase behavior and the order parameter under weak and strong shear of two different initial states, and realize the importance of the thermal history. It is necessary to apply the shear field at the appropriate time if we want to get what we want. These results provide an easy method to create ordered, defect-free materials in experiment and engineering technology through imposing shear flow. З метою дослiдження фазової поведiнки сумiшi блочний кополiмер/гомополiмер пiд дiєю сталої зсувової течiї використано моделювання динамiки комiрок. Фазовi переходи вiдбуваються вiд поперечної до
паралельної, а потiм до перпендикулярної ламеларної структури з ростом зсувової швидкостi, що є результатом взаємодiї мiж зсувовою течiєю i флуктуацiями концентрацiї. Усi реологiчнi властивостi, такi як
рiзницi нормального напруження i зсувова в’язкiсть, тiсно пов’язанi з напрямком ламели. Бiльше того,
зокрема нами дослiджено фазову поведiнку i параметр порядку при слабкому i сильному зсувовi двох рiзних початкових станiв, з врахуванням при цьому важливостi термiчної iсторiї. Для одержання бажаного
результату зсувове поле слiд прикласти у вiдповiдний момент часу. Результати цiєї роботи забезпечують
легкий спосiб створення впорядкованих бездефектних матерiалiв як в експериментi, так i в iнженернiй
технологiї за рахунок введення зсувової течiї.